Youth Employment Paths in a Ghanaian Rural Community - Peter Dwumah; Kofi Osei Akuoko; Eric Henry Yeboah; Nelson Gyasi-Boadu; Mary Sefa Boampong (E-Journal of Humanities, Arts and Social Sciences, 2023)
Rural youth engage in different employment activities. Due to the scarcity of literature on the employment activities and aspirations of youth in rural communities especially in Africa, the study examined the past, present and future employment of the out-of-school youth in Amankyea, a rural community in the Atwima Nwabiagya district of Ashanti Region in Ghana. Three (3) focus group discussions and interviews with 20 rural youth who were purposively selected were conducted. Questionnaires were also administered to 270 randomly selected young people in the rural community. The data analysis revealed that the rural youth engage in farming, formal employment, employment in informal enterprises, informal self-employment and family employment. Although the majority of young people were farming, most of them indicated their interest in informal self-employment as their future employment aspiration. The study recommends that farming should be made more attractive for the rural youth to choose as an employment aspiration. Rural youth should also be given skills training to enable them pursue self-employment.